The Suramadu Bridge Affair: Un-bridging the State and the Kyai in New Order Madura - Pribadi, Yanwar (Studia Islamika, 2015)
This paper by and large explores state-society relations and for the most part discusses the Indonesian government’s plans to ‘modernize’ Madura during the New Order administration and how a number of kyai responded to these plans. Specifically, it is concerned with a conflict between the state and the kyai in the Suramadu Bridge Affair, particularly in the rejection of the industrialization scheme by the Kyai of Bassra. An obvious aspect that can be highlighted from the conflict is the inability of state officials, especially at regional levels, to cope with the high expectations of the central government. Another central aspect underlined is the undemocratic approach of the government towards the implementation of its plans. The government’s plans to ‘modernize’ Madura eventually created resistance among some segments in society, and they made use of, among other things, Islamic symbols in resisting the government’s plans.DOI: 10.15408/sdi.v22i2.1919